Water Balance and Crop Yields: a Case Study of Groundnut - Ramachandran, V S; Rajegowda, M B (Annals of Arid Zone, 2016)
Associations between groundnut (Arachis hypogaea L.) kernel yield and the components of water balance were studied in the tropical semi-arid climate of Bangalore. Linear correlation coefficients and regression equations between seed yield and the water balance components revealed that rainfall. moisture index. water surplus and moisture adequacy ratio were positively correlated while potential evapo-transpiration,actual evapo-transpiration, water deficit and aridity index were negatively correlated.Prolonged spell of low cropwater- stress index during early vegetative and flowering stages reduced the kernel yields.